(untitled) (European Journal of Formal Sciences and Engineering, 2023)
In this article, I intend to carry out a hermeneutic study into the relationship between the workings of memory and landscape, and the consequences that such a relationship produces for living on an ethical level. In the first part, I intend to highlight the active role played by memory in the significant interpretations of the landscape. In consideration of this aspect, I will deal with the circularity between building a narrative of the landscape and exercising individual and collective memory. In the second part, I will focus on the role that the narrative, together with memory, plays with regard to the different forms of living. In the light of such activity, living is seen as ethical dwelling for the care of the landscape and of man who inhabits it.